Tales from Inside the Iron Lung (And How I Got Out of It) - Woods, Regina (University of Pennsylvania Press, 2016)
Regina Woods, just weeks before her fourteenth birthday contracted polio. Within a few days, she was paralyzed from the neck down, unable even to breathe by herself. What is most profound about this book is that--while it is an account of catastrophic loss--there is so much triumph in it.